The Effect of the Application of Tpack-Based Learning on the Motivation and Learning Achievement of Students of Public Elementary School 1 Sokanandi on PJOK Lessons - Imam Santosa (UM Purwokerto Press, 2025)
This study aims to determine the effect of the application of TPACK-based learning on the learning motivation of SD Negeri 1 Sokanandi students towards PJOK lessons. The type of research used is pseudo-experimental research using control classes and experimental classes. Student learning motivation data is measured using a questionnaire instrument while learning achievement uses a post test instrument. The data obtained was analyzed using the help of SPSS 2023 for windows. From the results of the analysis, it was found that there was an effect of the application of TPACK-based learning on student motivation and learning achievement at SD Negeri 1 Sokanandi in PJOK lessons.